2017
DOI: 10.1038/sj.bdj.2017.272
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness of undergraduate dental students in the United Kingdom: a national study

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
108
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(141 citation statements)
references
References 24 publications
25
108
2
6
Order By: Relevance
“…Regarding the clinical skills, over 70% of the participants in this study reported competence in obtaining a medical history; obtaining a valid consent for treatment; administering inferior alveolar nerve blocks; caries removal; and providing tooth fillings using amalgam and tooth‐coloured materials independently. These findings are similar to those reported in studies on graduates from Europe …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding the clinical skills, over 70% of the participants in this study reported competence in obtaining a medical history; obtaining a valid consent for treatment; administering inferior alveolar nerve blocks; caries removal; and providing tooth fillings using amalgam and tooth‐coloured materials independently. These findings are similar to those reported in studies on graduates from Europe …”
Section: Discussionsupporting
confidence: 92%
“…The participants reported inadequate experience in undertaking intraoral radiographs; only 7.3% students felt prepared in undertaking bitewing radiographs while 25% felt competent in undertaking periapical radiographs. In contrast, majority of students from United Kingdom reported competence in undertaking intraoral radiographs . The lack of competence reported by the Pakistani graduates may be explained by deficient training in undertaking routine dental radiography.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations